Pyrolytic carbon powder, method for producing the same, and use thereof
Patent Information
- Application Number
- CN202610208390.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-12
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-02-12
AI Technical Summary
[0004]然而,直接利用天然气制备热解碳面临几个难题:(1)衬底比表面积限制:热解碳的沉积效率依赖于衬底表面积;(2)均相成核干扰:反应空间过大时,极易生成炭黑杂质;(3)传热不均:低密度碳粉衬底导热性差,传统外部加热难以在反应器中心形成均匀热场
1、本发明的制备方法通过构建微米级受限反应空间来抑制炭黑生成,从而使碳源气体发生热解反应后进行异相沉积,为形成高纯的热解碳粉体提供必要条件;
Smart Images

Figure CN122520028B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of carbon material preparation and chemical vapor deposition, and particularly relates to a pyrolytic carbon powder, its preparation method and application. Background Technology
[0002] Natural gas, a high-quality carbon source, is primarily composed of methane. For a long time, natural gas has been industrially cracked at high temperatures to produce carbon black. In traditional carbon black production processes, natural gas is cracked in a high-temperature, spacious open environment, where carbon-containing free radicals undergo dehydrogenation and combine, forming disordered carbon particles (i.e., carbon black) through homogeneous nucleation. However, carbon black has a low added value and a low degree of graphitization.
[0003] To obtain carbon materials with higher economic value (such as high-purity graphite or pyrolytic carbon), it is generally necessary to suppress homogeneous nucleation and promote heterogeneous nucleation. Current graphite production mostly uses natural graphite, petroleum coke, or needle coke as raw materials, which inherently have high levels of heavy element impurities, leading to long, energy-intensive, and heavily polluting subsequent purification processes. In contrast, natural gas has very few impurities, making it an ideal raw material for preparing high-purity carbon materials.
[0004] However, the direct use of natural gas to prepare pyrolytic carbon faces several challenges: (1) substrate specific surface area limitation: the deposition efficiency of pyrolytic carbon depends on the substrate surface area; (2) homogeneous nucleation interference: when the reaction space is too large, carbon black impurities are easily generated; (3) uneven heat transfer: the low-density carbon powder substrate has poor thermal conductivity, and traditional external heating is difficult to form a uniform heat field in the center of the reactor.
[0005] Therefore, developing a process route that can effectively suppress carbon black formation, achieve uniform heating, and efficiently prepare high-purity pyrolytic carbon has significant application value. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a pyrolytic carbon powder, its preparation method, and its applications. This preparation method features a uniform thermal field, low carbon black byproduct production, high product purity, and high energy efficiency, making it suitable for the preparation of high-purity carbon materials. Specifically, this method enables the carbon source gas to undergo heterogeneous deposition in a micron-sized confined reaction space, which suppresses carbon black formation. Simultaneously, the Joule heating generated on the powder bed effectively solves the heat transfer problem, achieving uniform heating and thus producing high-purity pyrolytic carbon powder.
[0007] The present invention achieves the above objectives through the following technical solutions: This invention provides a method for preparing pyrolytic carbon powder, which includes the following steps: S1. A conductive carbon-based powder is loaded into a reactor to form a powder bed; wherein the apparent density of the carbon-based powder is 5-100 g / L. S2. Adjust the pore structure of the powder bed to form a confined reaction space with an average equivalent pore size of 10-1000μm. S3. Apply an electric current to the powder bed to generate Joule heat and raise the temperature to 1100-1500℃. S4. Introduce carbon source gas into the reactor and simultaneously apply mechanical disturbance to the powder bed to cause the carbon source gas to undergo a pyrolysis reaction and perform heterogeneous deposition on the surface of the carbon-based powder to obtain pyrolytic carbon powder.
[0008] In this invention, the apparent density of the carbon-based powder can be referred to as the bulk density, which affects the average equivalent pore size of the carbon-based powder, thereby affecting the effect of heterogeneous deposition.
[0009] In this invention, carbon-based powder with an apparent density of 5-100 g / L is a carbon-based powder with a low apparent density. It is used as a deposition substrate in the reactor to form a confined reaction space with an average equivalent pore size of 10-1000 μm.
[0010] In step S4 of this invention, the heterogeneous deposition process involves the deposition of carbon free radicals (or "carbon-containing active elements") generated by the pyrolysis of the carbon source gas onto the surface of the carbon-based powder serving as the deposition substrate, thereby enabling nucleation and growth on the surface of the carbon-based powder. The mechanical disturbance is used to reduce agglomeration and maintain the gas permeability and electrical resistance stability of the powder bed.
[0011] In this invention, the average equivalent pore size corresponds to the equivalent spacing between carbon-based powders. In the absence of a catalyst in the reaction process, the physical environment (especially the surface area to volume ratio (S / V)) is the primary driving factor for carbon structure formation. This invention controls the average equivalent pore size of the powder bed to enable the carbon source gas to undergo pyrolysis within a confined reaction space, thereby promoting heterogeneous deposition while strictly suppressing homogeneous nucleation. The pyrolysis process is as follows: in narrow channels (e.g., micrometer-scale channels), the surface area to volume ratio (S / V) is very high, and the carbon free radicals (or "carbon-containing active building blocks") generated by the pyrolysis of the carbon source gas diffuse to the channel walls via a very short path, thus forming graphite. The channel walls act as templates, lowering the nucleation energy barrier, allowing free radicals to deposit on the surface and rearrange, forming a layered ordered structure.
[0012] To ensure the carbon source gas decomposes into graphite rather than fumed carbon black, the maximum critical channel size depends on a competition between: molecular diffusion to the wall and the induction time for homogeneous nucleation. For the process to favor graphite formation, the time t required for carbon-containing radicals to reach the wall is also crucial. diff It must be much shorter than the time it takes for these free radicals to collide and nucleate into carbon black in the gas phase. soot In a channel of width w, the characteristic time for a free radical to reach the wall is t. diff ~ w 2 / D, where D is the diffusion coefficient. Taking 1200°C and 1 atm as an example, D is approximately 10 for small molecule hydrocarbons. -4 Up to 10 -3 m 2 / s. At 1200°C, the induction time for methane to form carbon black is typically in the range of 10 to 50 milliseconds. Typical values using 1200°C and 1 atm: t soot = 0.02 seconds, D = 5 × 10 -4 m 2 / s, we can get w = 0.003 m, which means that the theoretical maximum critical size of the channel is about 3 mm (3,000 μm). However, in actual high-purity graphite deposition projects, a smaller "safe" width is usually adopted to take into account local concentration gradients and gas phase residence time.
[0013] In some embodiments, in step S1, the apparent density of the carbon-based powder is 5-30 g / L.
[0014] In some embodiments, in step S1, the carbon-based powder is selected from one or more of chopped carbon fibers, carbonized PAN, worm graphite, carbon black, carbon nanotubes, and graphitized micropowder.
[0015] In a specific embodiment, the carbon-based powder is selected from chopped carbon fibers, the length of which is 0.2-2 mm; preferably, the length of which is 0.5-1 mm. Chopped carbon fibers of the above-mentioned length are selected to match the particle size and morphology of the carbon-based powder.
[0016] In some embodiments, in step S2, the pore structure of the powder bed is controlled by one or more of the following methods: grading the particle size and morphology of the carbon-based powder, vibrating and shaping the powder bed, and applying compaction pressure to the powder bed.
[0017] In a specific implementation, when the method of controlling the pore structure of the powder bed includes vibrating and shaping the powder bed, the vibration and shaping includes continuously or periodically mechanically disturbing the powder bed.
[0018] In a specific implementation, when the method for controlling the pore structure of the powder bed includes applying compaction pressure to the powder bed, the compaction pressure is 0-0.5 MPa, but not 0; preferably, the compaction pressure is 0.05 MPa. Here, the compaction pressure refers to the pressure relative to the external environment.
[0019] In this invention, the main factor affecting the average equivalent pore size of the powder bed is the apparent density (or "bulk density") of the carbon-based powder, which in turn affects the heterogeneous deposition of the pyrolysis reaction; in addition, the porosity of the powder bed also affects the average equivalent pore size of the powder bed.
[0020] In some embodiments, in step S2, the average equivalent pore size of the powder bed is 20-50 μm.
[0021] In some embodiments, in step S2, the porosity of the powder bed is 40%-99.5%.
[0022] In step S3 of this invention, after the cross-section of the powder bed is fixed, a corresponding resistor can be obtained; the magnitude of the current through this resistor determines the power applied to the powder bed. This can be determined based on the heating power (P=I). 2 The heating rate and the maximum heating temperature are determined by the heat dissipation power (×R) and the heat sink power.
[0023] In this invention, the thickness of the powder bed is related to the gas flow rate of the carbon source gas in step S4; under a specified reaction temperature, the time for the carbon source gas to pass through the powder bed is 10 seconds or more, preferably 20 seconds or more; the flow velocity of the carbon source gas penetrating the powder bed is 5 mm / s or more, preferably 20 mm / s or more. According to calculation methods in the art, the thickness of the powder bed can be calculated based on the cross-section of the powder bed and the gas flow rate.
[0024] In some embodiments, in step S4, the carbon source gas includes natural gas.
[0025] In a specific implementation, the volume fraction of methane in the natural gas is 60%-100%.
[0026] In a specific implementation, the carbon source gas is a mixture of natural gas and inert gas.
[0027] In some implementations, in step S4, the mechanical disturbance is one or more of stirring, tumbling, vibration, and pulse compaction.
[0028] In some embodiments, in step S4, the reaction pressure of the pyrolysis reaction is 0.1-2 atm, preferably 0.5-1.2 atm.
[0029] In some embodiments, during step S4, as carbon deposition continues, the relative change rate of the resistivity of the powder bed may exceed 20%. Preferably, the relative change rate of the resistivity of the powder bed is controlled to be less than or equal to 20%. By controlling the relative change rate of the resistivity of the powder bed within this range, the resistance of the powder bed remains relatively stable, thereby improving the uniformity of Joule heating generated throughout the powder bed.
[0030] In a specific implementation, the control method includes: monitoring the resistance or voltage and current parameters of the powder bed and performing closed-loop adjustment to ensure that the relative change rate of the resistance of the powder bed during the deposition process is less than or equal to 20%; wherein, the formula for calculating the relative change rate of resistance is ΔR / R0 (ΔR is the resistance change value, and R0 is the initial resistance).
[0031] In this invention, a powder bed is formed by stacking carbon-based powders with low apparent density, and the size of the voids between particles is controlled by means of powder shape and the application of mechanical pressure. These tiny voids constitute a confined reaction space, forcing carbon free radicals generated by the decomposition of carbon source gas to contact the surface of the powder bed before gas-phase collision, thereby causing heterogeneous deposition and forming a dense pyrolytic carbon powder.
[0032] In some embodiments, the preparation method is carried out in a pyrolytic carbon powder preparation apparatus, which includes: a reactor, an insulating liner, a bed shaping mechanism, a disturbance component, an electrode assembly, an electrical parameter acquisition and closed-loop control unit, and a gas supply and distribution component. The insulating liner is installed inside the reactor and is used to load the powder bed. The bed shaping mechanism is used to compact and / or vibrate the powder bed to regulate the pore structure of the powder bed; The disturbance component is used to mechanically disturb the powder bed; The electrode assembly is used to clamp the powder bed and apply current to the powder bed, and the electrode assembly is electrically connected to the electrical parameter acquisition and closed-loop control unit; The electrical parameter acquisition and closed-loop control unit is used to adjust the current or voltage output according to the resistance of the powder bed, the input power and / or the temperature signal of the powder bed; The gas supply and distribution assembly is connected to the gas inlet of the reactor.
[0033] The electrode assembly is kept in close contact with the powder bed to ensure that the electrode can smoothly apply current to the powder bed.
[0034] In a specific implementation, the insulating liner is a high-temperature resistant ceramic or carbon-based composite insulating structure to reduce the risk of metal contamination.
[0035] In specific embodiments, the disturbance components include a stirring paddle, a drum tilting mechanism, a vibrator, or a pulse compaction mechanism. The reaction chamber with a lower apparent density contains a large amount of compressible space, which the stirring paddle blades utilize to disturb the powder bed. Even as the apparent density of the pyrolytic carbon powder increases to approximately 1 g / L, disturbance can still be achieved using the space above the powder bed to control the temperature of that space and prevent homogeneous nucleation reactions from occurring within it.
[0036] In a specific implementation, the electrode assembly is one or more of the following: end plate electrode, ring electrode, and electrode rod.
[0037] The present invention also provides a pyrolytic carbon powder, which is prepared by the preparation method described above; the pyrolytic carbon powder includes a carbon-based core and a pyrolytic carbon shell, wherein the pyrolytic carbon shell coats the surface of the carbon-based core.
[0038] In this invention, the carbon-based core corresponds to the carbon-based powder in the preparation method, and the pyrolytic carbon shell corresponds to the graphite layer deposited heterogeneously on the surface of the carbon-based powder by pyrolysis of the carbon source gas in the preparation method. The proportion of the graphite layer in the pyrolytic carbon powder can be evaluated using the symmetry of the XRD (002) peak of graphite.
[0039] In some embodiments, the thickness of the pyrolytic carbon shell is 10-500 μm.
[0040] In some embodiments, the metal impurity content of the pyrolytic carbon powder is ≤100 ppm.
[0041] In some embodiments, the carbon-based core is selected from one or more of chopped carbon fibers, carbonized PAN, worm graphite, carbon black, carbon nanotubes, and graphitized micropowder.
[0042] In this invention, the mass fraction of ultrafine particles (based on the particle size threshold defined by gradation) in the pyrolytic carbon powder is not higher than a preset threshold, so as to characterize that carbon black byproducts are suppressed.
[0043] The present invention also provides an application of the pyrolytic carbon powder as described above in lithium-ion battery anode materials, conductive additives, wear-resistant fillers, sealing fillers, or high-temperature composite materials.
[0044] Compared with the prior art, the present invention has the following significant advantages: 1. The preparation method of the present invention suppresses the generation of carbon black by constructing a micron-level confined reaction space, thereby enabling the carbon source gas to undergo a pyrolysis reaction and then undergo heterogeneous deposition, providing the necessary conditions for the formation of high-purity pyrolytic carbon powder. 2. This invention forms a powder bed from loose carbon-based powder. To address the problem of poor thermal conductivity, this invention adopts a "direct Joule heating" mode, applying current to the conductive carbon powder bed and using in-situ Joule heating of the substrate to make the substrate heat up uniformly from the inside out. At the same time, mechanical stirring is used to prevent the carbon-based powder from agglomerating due to deposition and growth, and to ensure the uniformity of the powder bed resistance and smooth gas flow, providing the necessary conditions for the formation of high-purity pyrolytic carbon powder. Attached Figure Description
[0045] Figure 1 This is a SEM image of the pyrolytic carbon powder prepared by the method in Example 1 of this application; Figure 2 This is a SEM image of the pyrolytic carbon powder prepared by the method in Example 2 of this application; Figure 3 This is a SEM image of the pyrolytic carbon powder prepared by the method in Example 2 of this application; Figure 4 The image shows the XRD pattern of the pyrolytic carbon powder prepared by the method in Example 2 of this application. Figure 5 These are XRD comparison images of the pyrolytic carbon powders prepared in Examples 1-2 and Comparative Example 1 of this application; Figure 6 This is a comparative schematic diagram showing the deposition effects in Example 1 and Comparative Example 2 of this application. Detailed Implementation
[0046] The present invention will be further described in detail below through preferred embodiments, but the scope of protection of the present invention is not limited thereto.
[0047] Example 1 This embodiment discloses a pyrolytic carbon powder and its preparation method.
[0048] The preparation method includes the following steps: S1. A conductive carbon-based powder is used as a deposition substrate and loaded into a reactor with an insulating liner to form a powder bed with a height of 1m; wherein the carbon-based powder is selected from PAN-based (polyacrylonitrile) short-cut carbon fibers with a length of 0.5-1mm and an apparent density of 7 g / L. S2. The powder bed is then subjected to vibration shaping and compaction pressure of 0.01 MPa in sequence to regulate the pore structure of the powder bed and form a confined reaction space with an average equivalent pore size of 50 μm. S3. Clamp the electrodes at both ends of the powder bed, apply current to the powder bed to generate Joule heating and raise the temperature to 1200-1350℃, maintain the temperature fluctuation ≤±30℃ through voltage / current closed loop, and make the relative change rate of the powder bed resistance less than or equal to 20%; S4. Natural gas vaporized from LNG (liquefied natural gas) is introduced into the reactor, and mechanical disturbance is applied to the powder bed at a speed of 10-50 rpm or equivalent disturbance intensity to cause the natural gas to undergo pyrolysis reaction and heterogeneous deposition on the surface of carbon-based powder to obtain pyrolytic carbon powder. S5. Stop the ventilation and power supply, protect and cool under an inert atmosphere, and collect the product.
[0049] Figure 1 This is a SEM image of the pyrolytic carbon powder prepared by the method of this embodiment. The pyrolytic carbon powder obtained by the above method has a core-shell structure, with the core being carbon-based powder and the shell being a pyrolytic carbon layer. Compared with the homogeneous nucleation process carried out in an open space, the agglomeration of the pyrolytic carbon powder is significantly reduced.
[0050] The preparation method described in this embodiment is carried out in a pyrolytic carbon powder preparation apparatus. The apparatus includes: a reactor, an insulating liner, a bed shaping mechanism, a disturbance component, an electrode assembly, an electrical parameter acquisition and closed-loop control unit, and a gas supply and distribution component. The insulating liner is located inside the reactor and is used to load the powder bed. The bed shaping mechanism is used to compact and / or vibrate the powder bed to regulate its pore structure. The disturbance component is used to mechanically disturb the powder bed. The electrode assembly is used to clamp the powder bed and apply current to it, and is electrically connected to the electrical parameter acquisition and closed-loop control unit. The electrical parameter acquisition and closed-loop control unit is used to adjust the current or voltage output based on the powder bed's resistance, input power, and / or temperature signal. The gas supply and distribution component is connected to the reactor's inlet. The insulating liner is a high-temperature resistant ceramic or carbon-based composite insulating structure. The disturbance component includes a stirring paddle. The electrode assembly consists of end plate electrodes.
[0051] Example 2 This embodiment discloses a pyrolytic carbon powder and its preparation method.
[0052] The preparation method uses the same process and conditions as in Example 1, but differs from Example 1 in that: In step S1, PAN carbonized fiber with a diameter of 20 μm and a length of 1 mm is used as the deposition substrate; In step S2, the compaction pressure on the powder bed is increased to compact the apparent density of the carbon-based powder to 15 g / L, so that the powder bed forms a confined reaction space with an average equivalent pore size of 30 μm.
[0053] In step S4, a higher frequency mechanical disturbance is applied to the powder bed to avoid the problem of increased pressure drop or decreased permeability caused by the reduction in the average equivalent pore size of the powder bed.
[0054] Compared to Example 1, this example reduces the average equivalent pore size of the powder bed to enhance the confined space effect during heterogeneous deposition.
[0055] Figure 2 and Figure 3 All images are SEM images of the pyrolytic carbon powder prepared by the method described in this embodiment; among them, Figure 2 This is a SEM image of pyrolytic carbon powder at a resolution of 500 μm. Figure 3 This is a SEM image of pyrolytic carbon powder at a resolution of 5 μm. Figure 4 The image shows the XRD pattern of the pyrolytic carbon powder prepared by the method of this embodiment. The pyrolytic carbon powder obtained by the method of this embodiment has a core-shell structure, with the core being carbon-based powder and the shell being a pyrolytic carbon layer; compared with the pyrolytic carbon powder of Example 1, the carbon black byproducts in this pyrolytic carbon powder are further reduced.
[0056] Example 3 This embodiment discloses a pyrolytic carbon powder and its preparation method.
[0057] The preparation method uses the same process and conditions as in Example 1, but differs from Example 1 in that: In step S1, worm graphite is used as the deposition substrate. Through particle size and morphology gradation and compaction of carbon-based powder, the average equivalent pore size of the powder bed is still 50 μm.
[0058] The pyrolytic carbon powder obtained by the above method has a core-shell structure, with the core being a carbon-based powder and the shell being a pyrolytic carbon layer. By using different materials as the core of the pyrolytic carbon powder, the shell texture and its final electrical and thermal properties can be altered.
[0059] Comparative Example 1 This comparative example discloses a pyrolytic carbon powder and its preparation method.
[0060] The preparation method includes the following steps: S1. A conductive carbon-based powder is used as a deposition substrate and loaded into a reactor with an insulating liner to form a powder bed with a height of 1m; wherein the carbon-based powder is selected from PAN-based (polyacrylonitrile) short-cut carbon fibers with a length of 0.5-1mm and an apparent density of 7 g / L. S2. Clamp the electrodes at both ends of the powder bed, apply current to the powder bed to generate Joule heating and raise the temperature to 1200-1350℃, maintain the temperature fluctuation ≤±30℃ through voltage / current closed loop, and make the relative change rate of the powder bed resistance less than or equal to 20%; S3. Natural gas vaporized from LNG (liquefied natural gas) is introduced into the reactor to cause the natural gas to undergo a pyrolysis reaction and be deposited on the surface of carbon-based powder; S4. Stop the ventilation and power supply, protect and cool under an inert atmosphere, and collect the product.
[0061] In this comparative example, the powder bed was not compacted or its porosity was not controlled, resulting in coarse pores in the powder bed (equivalent pore size > 1000 μm).
[0062] Because the powder bed in this comparative example did not form a confined space and had excessively large pores, pyrolytic carbon was more prone to homogeneous nucleation, resulting in a significantly higher proportion of amorphous carbon (carbon black) and poor crystal structure in the product. Characterization using grading / particle size distribution / specific surface area revealed an increased proportion of ultrafine particles and a decreased density in the core-shell layer.
[0063] Comparative Example 2 This comparative example discloses a pyrolytic carbon powder and its preparation method.
[0064] The preparation method includes the following steps: S1. A conductive carbon-based powder is used as a deposition substrate and loaded into a reactor with an insulating liner to form a powder bed with a height of 1m; wherein the carbon-based powder is selected from PAN-based (polyacrylonitrile) short-cut carbon fibers with a length of 0.5-1mm and an apparent density of 7 g / L. S2. The powder bed is then subjected to vibration shaping and compaction pressure of 0.01 MPa in sequence to regulate the pore structure of the powder bed and form a confined reaction space with an average equivalent pore size of 50 μm. S3. Use an external furnace to heat the powder bed to 1200-1350℃; S4. Natural gas vaporized from LNG (liquefied natural gas) is introduced into the reactor, and mechanical disturbance is applied to the powder bed at a speed of 10-50 rpm or equivalent disturbance intensity to cause the natural gas to undergo pyrolysis reaction and heterogeneous deposition on the surface of carbon-based powder to obtain pyrolytic carbon powder. S5. Stop the ventilation and power supply, protect and cool under an inert atmosphere, and collect the product.
[0065] Figure 6 This is a comparative schematic diagram showing the deposition effects in Example 1 and Comparative Example 2 of this application; wherein, Figure 6a is a schematic diagram of the heterogeneous deposition effect in Embodiment 1 of this application. Figure 6 b is a schematic diagram of the deposition effect in Comparative Example 2. For example... Figure 6 As shown in Figure a, the use of electric heating generates Joule heating in the powder bed, allowing pyrolytic carbon to deposit throughout the entire powder bed, resulting in a uniform product. Figure 6 As shown in b, due to the low apparent density and poor thermal conductivity of carbon-based powders, the center of the powder bed cannot reach the set temperature, causing pyrolytic carbon to be deposited only on the outer layer of the powder bed and difficult to deposit in the center. This results in uneven deposition due to the temperature difference between the inside and outside of the bed, increasing the risk of local agglomeration, and making it difficult to stably control the process resistance / permeability.
[0066] Example 1 The purity of the pyrolytic carbon powder was determined in this example; the pyrolytic carbon powder prepared in Examples 1 and 2 was detected by X-ray diffraction (XRD) and inductively coupled plasma spectroscopy (IPC).
[0067] Figure 5 The images show a comparison of the XRD patterns of the pyrolytic carbon powders prepared in Examples 1-2 and Comparative Example 1. Figure 5 In the diagram, the black line corresponds to the product of Comparative Example 1, the red line corresponds to the product of Example 1, and the blue line corresponds to the product of Example 2. Due to the homogeneous nucleation reaction that occurred during the process, the graphitization degree of the product of Comparative Example 1 was 86.9%. Example 1 underwent heterogeneous deposition, resulting in a graphitization degree of 93.1% for its product. Example 2 optimized the powder bed and further pressurized it, achieving a graphitization degree of 94.9% for its product.
[0068] In addition, Table 1 shows the results of impurity content in the pyrolytic carbon powder of Examples 1-2.
[0069] Table 1
[0070] It is evident that the metal impurities in the products of Examples 1 and 2 can be controlled at a low level.
[0071] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing pyrolytic carbon powder, characterized in that, It includes the following steps: S1. A conductive carbon-based powder is loaded into a reactor to form a powder bed; wherein the apparent density of the carbon-based powder is 5-100 g / L. S2. Adjust the pore structure of the powder bed to form a confined reaction space with an average equivalent pore size of 10-1000 μm; the average equivalent pore size is equivalent to the equivalent spacing between carbon-based powders. S3. Apply an electric current to the powder bed to generate Joule heat and raise the temperature to 1100-1500℃. S4. Introduce carbon source gas into the reactor while simultaneously applying mechanical disturbance to the powder bed to cause the carbon source gas to undergo a pyrolysis reaction and to perform heterogeneous deposition on the surface of the carbon-based powder to obtain pyrolytic carbon powder; the carbon source gas includes natural gas.
2. The preparation method according to claim 1, characterized in that, Step S1 satisfies at least one of the following conditions: i. The apparent density of the carbon-based powder is 5-30 g / L; ii. The carbon-based powder is selected from one or more of the following: chopped carbon fibers, carbonized PAN, worm graphite, carbon black, carbon nanotubes, and graphitized micro powder.
3. The preparation method according to claim 2, characterized in that, The carbon-based powder is selected from chopped carbon fibers, the length of which is 0.2-2 mm.
4. The preparation method according to claim 3, characterized in that, The length of the chopped carbon fiber is 0.5-1 mm.
5. The preparation method according to claim 1, characterized in that, Step S2 satisfies at least one of the following conditions: i. The method for controlling the pore structure of the powder bed is one or more of the following: grading the particle size and morphology of the carbon-based powder, vibrating and shaping the powder bed, and applying compaction pressure to the powder bed; ii. The average equivalent pore size of the powder bed is 20-50 μm; iii. The porosity of the powder bed is 40%-99.5%.
6. The preparation method according to claim 5, characterized in that, In step S2, when the method of controlling the pore structure of the powder bed includes vibrating and shaping the powder bed, the vibration and shaping includes continuously or periodically mechanically disturbing the powder bed. When the method of controlling the pore structure of the powder bed includes applying a compaction pressure to the powder bed, the compaction pressure is 0-0.5 MPa, but not 0.
7. The preparation method according to claim 6, characterized in that, The compaction pressure is 0.05 MPa.
8. The preparation method according to claim 1, characterized in that, Step S4 satisfies at least one of the following conditions: i. The volume fraction of methane in the natural gas is 60%-100%; the carbon source gas is a mixture of natural gas and inert gas; ii. The mechanical disturbance is one or more of stirring, tumbling, vibration, and pulse compaction; iii. The reaction pressure of the pyrolysis reaction is 0.1-2 atm; iv. During the heterogeneous deposition process, the relative change rate of the resistivity of the powder bed is controlled to be less than or equal to 20%.
9. The preparation method according to claim 2, characterized in that, The reaction pressure of the pyrolysis reaction is 0.5-1.2 atm.
10. The preparation method according to any one of claims 1-9, characterized in that, The preparation method is carried out in a pyrolytic carbon powder preparation device, which includes: a reactor, an insulating liner, a bed shaping mechanism, a disturbance component, an electrode component, an electrical parameter acquisition and closed-loop control unit, and a gas supply and distribution component. The insulating liner is installed inside the reactor and is used to load the powder bed. The bed shaping mechanism is used to compact and / or vibrate the powder bed to regulate the pore structure of the powder bed; The disturbance component is used to mechanically disturb the powder bed; The electrode assembly is used to clamp the powder bed and apply current to the powder bed, and the electrode assembly is electrically connected to the electrical parameter acquisition and closed-loop control unit; The electrical parameter acquisition and closed-loop control unit is used to adjust the current or voltage output according to the resistance of the powder bed, the input power and / or the temperature signal of the powder bed; The gas supply and distribution assembly is connected to the gas inlet of the reactor.
11. The preparation method according to claim 10, characterized in that, The pyrolysis carbon powder preparation apparatus satisfies at least one of the following conditions: i. The insulating lining is a high-temperature resistant ceramic or carbon-based composite insulating structure; ii. The disturbance component includes a stirring paddle, a drum tilting mechanism, a vibrator, or a pulse compaction mechanism; iii. The electrode assembly is one or more of the following: end plate electrode, ring electrode, and electrode rod.
12. A pyrolytic carbon powder, characterized in that, It is prepared by the preparation method according to any one of claims 1-11; the pyrolytic carbon powder includes a carbon-based core and a pyrolytic carbon shell, wherein the pyrolytic carbon shell coats the surface of the carbon-based core.
13. The pyrolytic carbon powder as described in claim 12, characterized in that, The pyrolytic carbon powder satisfies at least one of the following conditions: i. The thickness of the pyrolytic carbon shell is 10-500 μm; ii. The metal impurity content of the pyrolytic carbon powder is ≤100 ppm; iii. The carbon-based core is selected from one or more of the following: short-cut carbon fibers, carbonized PAN, worm graphite, carbon black, carbon nanotubes, and graphitized micro powder.
14. The application of the pyrolytic carbon powder as described in claim 12 or 13 in lithium-ion battery anode materials, conductive additives, wear-resistant fillers, sealing fillers, or high-temperature composite materials.
Citation Information
Patent Citations
Pyrolytic graphite composite coating and applications thereof
CN101660137A
Method and device for preparing carbon nanotube and hydrogen
CN113135562A